Knowledge landscape of macrophage research in liver fibrosis: a bibliometric review of the literature from WoSCC - Yanbo Li; Zhengmin Cao; Yanping Lu; Chao Lei; Wenliang Lyu (Frontiers in Pharmacology)
Recent insights into the immune response in fibrosis have provided valuable perspectives for the treatment of liver fibrosis. Macrophages, as the most abundant immune cells in the liver, are key drivers of liver fibrosis. They are extensively involved in tissue damage, chronic inflammation, and the progression and regression of liver fibrosis. This study aims to conduct a bibliometric analysis and literature review on the mechanisms by which macrophages contribute to liver fibrosis. Specifically, we analyzed a bibliometric dataset comprising 1,312 papers from 59 countries, 1,872 institutions, and 9,784 authors. Keyword co-occurrence analysis identified key research hotspots, including the role of macrophage subtypes in obesity-related metabolic disorders, the crosstalk between macrophages and hepatic stellate cells through mechanoimmunology, emerging strategies for immune modulation targeting macrophages to promote fibrosis regression and liver regeneration, and new discoveries regarding macrophage crosstalk with other immune cells. In conclusion, this study provides a visual analysis of the current research landscape, hotspots, and trends in the field of macrophages and liver fibrosis, and discusses future directions for further exploration in this area.